Approach to Hemoptysis in the Modern Era - Sébastien Gagnon; Nicholas Quigley; Hervé Dutau; Antoine Delage; Marc Fortin (Canadian Respiratory Journal)
Hemoptysis is a frequent manifestation of a wide variety of diseases, with mild to life-threatening presentations. The diagnostic workup and the management of severe hemoptysis are often challenging. Advances in endoscopic techniques have led to different new therapeutic approaches. Cold saline, vasoconstrictive and antifibrinolytic agents, oxidized regenerated cellulose, biocompatible glue, laser photocoagulation, argon plasma coagulation, and endobronchial stents and valves are amongst the tools available to the bronchoscopist. In this article, we review the evidence regarding the definition, etiology, diagnostic modalities, and treatment of severe hemoptysis in the modern era with emphasis on bronchoscopic techniques.